2018
DOI: 10.1007/s00404-018-4694-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of assisted reproductive technology on the incidence of birth defects among livebirths

Abstract: There is an overall and type-specific increased risk of birth defects in the ART population. Appropriate counseling and specialized ultrasound evaluations should be considered in pregnancies conceived by ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…For the 29‐year period, prevalence in our hospital for ONTDs was of 12.6 per 10 000 live births (Table 1). This is notably higher compared with other prevalences based on data limited to live‐born from countries such as the United States, 22 Canada, 23 Norway, 24 and Japan, 25 which range from 2.2 to 6.9 per 10 000 live births; despite the fact that in those countries around two‐thirds of cases do not achieve birth because are electively terminated after prenatal NTDs diagnosis. It also coincides with reports indicating that our co‐nationals living in the US have intriguingly an elevated rate of NTDs in comparison with other ethnicities, 8,26 which ranges from 3.9 to 5.8 per 10 000 live births.…”
Section: Discussionmentioning
confidence: 67%
“…For the 29‐year period, prevalence in our hospital for ONTDs was of 12.6 per 10 000 live births (Table 1). This is notably higher compared with other prevalences based on data limited to live‐born from countries such as the United States, 22 Canada, 23 Norway, 24 and Japan, 25 which range from 2.2 to 6.9 per 10 000 live births; despite the fact that in those countries around two‐thirds of cases do not achieve birth because are electively terminated after prenatal NTDs diagnosis. It also coincides with reports indicating that our co‐nationals living in the US have intriguingly an elevated rate of NTDs in comparison with other ethnicities, 8,26 which ranges from 3.9 to 5.8 per 10 000 live births.…”
Section: Discussionmentioning
confidence: 67%
“…More importantly, the birth defects most commonly associated were cyanotic heart defects, with a frequency of 0.50% in the assisted reproductive technology group and 0.07% in the spontaneous pregnancy group. 25 This is supported by another study by Shamshirsaz et al who also discovered that fertility treatments led to increased risks in the development of foetal cyanotic heart defects. 26 It is thought that along with the process of the treatment itself, the parental subfertile substrate may also be an underlying mechanism, and hence the use of assisted reproductive technology warrants screening via fetal echocardiography.…”
Section: Maternal Factorsmentioning
confidence: 81%
“…To date, several studies have indicated that ART use is associated with an increased risk of congenital anomalies ( 2 7 , 11 , 20 , 21 ). Levi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Their treatment is complicated, resulting in great psychological and financial burden on the child and his family. Recently, several studies have demonstrated that pregnancies conceived with IVF/ICSI have an increased risk of congenital anomalies compared to spontaneous conceptions (3)(4)(5)(6)(7), and some meta-analyses have concluded that the pooled risk estimation ranges from 1.32 to 1.37 (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%